Ceftazidime-resistance in pediatric melioidosis : A case report and literature review - Tonnii Sia, Loong Loong; Charles, Lai Dekun; Kamilah, Manan; Khiu, Fu Lung; Siti Zakiyyah, Bakhtiar; Chor, Yek Kee; Chien, Su Lin; Tan, Lee See; Ooi, Mong How; Anand, Mohan (Elsevier Ltd., 2025)
We report a first case of ceftazidime-resistant pediatric melioidosis involving a previously healthy seven-year-old boy who presented with right lobar pneumonia complicated with a 5-cm lung abscess. Ceftazidime was initiated on Day-6 of admission when Burkholderia pseudomallei (ceftazidime-susceptible, minimum inhibitory concentration [MIC] 1.0 mcg/mL) was isolated from blood. Despite ceftazidime therapy at the recommended dosage, he developed fulminant septic shock and respiratory failure on Day-18 of hospitalization, requiring invasive ventilation, hemodynamic support, and continuous renal replacement therapy. His antibiotic was empirically escalated to meropenem; ceftazidime-resistant B. pseudomallei (MIC 32 mcg/mL) was subsequently isolated from blood and endotracheal secretions. He improved after two weeks of intensive care and was discharged well after two months of hospitalization. Our literature review on ceftazidime-resistant B. pseudomallei infection indicates that acquired resistance is a rare but potentially lethal treatment-related complication. All melioidosis patients should be carefully monitored during treatment with ceftazidime (or other β-lactams) for the development of antimicrobial resistance.